Socioeconomic and biophysical characterization of agroecosystems in the municipality of Pasca in the province of Sumapaz-Cundinamarca - Fonseca - Carreño, Nelson Enrique (Universidad Francisco de Paula Santander, 2021)
Twelve farms in the municipality of Pasca were evaluated to determine the socioeconomic and biophysical characteristics through productive practices. Participatory methods, surveys and guided tours were used to capture information. Among the findings, agro-ecosystems respond to traditional production characteristics with a strong family incidence, responding to external factors such as lack of capital, low technology, market distortions, and adverse climate conditions. There is a strong link between rural inhabitants and agricultural activities through a link between available resources (land, water, biodiversity), well-being and food security of the family.